The Enlightenment of Technology Introduction from Japan and South Korea on China - Wang, Xiangying (Journal of Education and Educational Technologies, 2023)
The improvement of the competitiveness of advanced manufacturing industry cannot be separated from the optimization and upgrading of industrial institutions. The optimization and upgrading of industrial institutions provide an ecosystem for the improvement of the competitiveness of advanced manufacturing industry. Only by starting from the low-end manufacturing industry can the optimization and upgrading of industrial structure provide assistance for the improvement of high-end manufacturing industry. The article analyzes how to optimize industrial institutions and enhance the competitiveness of industries based on the selection of technology introduction policies in industrial technological progress.